THE INFLUENCE OF SERVICE QUALITY ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION MEDIATION AT BCE EXPRESS - Mega Jayanti; Arbi Siti Rabiah H.M (Suluh Adiluhung Publisher (SAPub), 2025)
The development of the service industry currently plays an important role in contributing to the country's economy. One type of service company is a goods delivery service company. This study aims to determine the effect of service quality on repurchase intention through customer satisfaction as a mediating variable at BCE Express Green Lake City. This research used a quantitative approach by using probability sampling and a simple random sampling technique, which was processed through path analysis. Samples in this study amounted to 100 respondents. The results achieved in this study are that service quality has a significant positive effect on customer satisfaction, service quality has a significant positive effect on repurchase intention, and customer satisfaction has a significant positive effect on repurchase intention. Another finding is that service quality has a significant positive effect on repurchase intention through the mediation of customer satisfaction.